Cytotoxicity of Combination Doxorubicin and Garcinia picrorrhiza Fruit Extract on Fibroblast Cell - Utami, Sri; Endrini, Susi; Batubara, Lilian; Rahmah, Nunung Ainur; Syarif, Irfan; Nafik, Said; Arrahmani, Betharie Cendera; Novianto, Agung; Kusuma, Hanna Sari Widya; Widowati, Wahyu (Universitas Islam Bandung, 2023)
Combining chemotherapeutic agents such as doxorubicin with herbal products or other compounds that can enhance cytotoxicity without side effects is required. Thus, we aimed to observe the cytotoxicity of doxorubicin and sesoot (Garcinia picrorrhiza) fruit ethanolic extract (GpKar) on human fibroblast cells, BJ. This study used a post-test-only control randomized group design with n=3 and a number group of 5. The method used in this research is cell number, and viability was measured with (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium assay. Treatments consisted of a combination of doxorubicin (0.02 μg/ml) and GpKar of 66.47 µg/ml (DES1), 132.94 µg/ml (DES2) and 265.89 μg/ml (DES3). The data were analyzed using a one-way ANOVA and Duncan post hoc tests. DES3 showed the lowest viability among treatments (89.32%). DES1 and DES2 showed high viability (>90%), 97.93%, and 95.08%, respectively. Thus, the combination of doxorubicin (0.02 μg/ml) and GpKar (66.47 µg/ml) was considered safe for further use in the following assay. In summary, the combination of doxorubicin and GpKar showed high viability in normal fibroblast cells.